Improving Students' Writing Ability through Tea Party Technique Using English Song - Frida Alifah; Tasrikha Ikawati; Umi Tursini; Teguh Sulistyo; Frida Alifah; Tasrikha Ikawati; Umi Tursini (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2023)
Writing might be a complex skill for the students rather than other three skills because there are many aspects that have to understand. Thus, to help students’ difficulty on writing, it needs the effective and efficient technique in teaching and learning process. This study aims to find out whether there is a significant improvement on students’ scores on writing ability through Tea Party Technique using English song. The population of this research was the eleventh grade students of SMA Negeri 8 Malang, and the sample was eleventh grade students of Science 1. Classroom Action Research was used as a research design. The technique included of planning, action, observing, and reflecting phases, and the research was applied in three cycles. The result of this study shows that there is significant improvement of students’ writing skill. It can be seen on students’ score in pre-test, middle test, and post-test. The average score of the students grew by 4.27 between the pre-test and middle test, and by 15.24 between the middle test and post-test. In short, the integration of the Tea Party Technique with English song can enhance students' writing skills, especially in writing descriptive text.